PDT with genetically encoded photosensitizer miniSOG on a tumor spheroid model: A comparative study of continuous-wave and pulsed irradiation - Yuzhakova, Diana V.; Shirmanova, Marina V.; Klimenko, Vladimir V.; Lukina, Maria M.; Gavrina, Alena I.; Komarova, Anastasya D.; Gorbachev, Dmitry A.; Sapogova, Natalya V.; Lukyanov, Konstantin A.; Kamensky, Vladislav A. (Biochimica et biophysica acta. General subjects, 2021)
Therapeutic effects of PDT depend on many factors, including the amount of singlet oxygen, localization of photosensitizer and irradiation protocol. The present study was aimed to compare the cytotoxic mechanisms of PDT under continuous-wave (CW) and pulsed irradiation using a tumor spheroid model and a genetically encoded photosensitizer miniSOG. 1O2 detection in miniSOG and flavin mononucleotide (FMN) solutions was performed. Photobleaching of miniSOG in solution and in HeLa tumor spheroids was analyzed. Tumor spheroid morphology and growth and the cell death mechanisms after PDT in CW and pulsed modes were assessed. We found a more rapid 1O2 generation and a higher photobleaching rate in miniSOG solution upon irradiation in pulsed mode compared to CW mode. Photobleaching of miniSOG in tumor spheroids was also higher after irradiation in the pulsed mode. PDT of spheroids in CW mode resulted in a moderate expansion of the necrotic core of tumor spheroids and a slight inhibition of spheroid growth. The pulsed mode was more effective in induction of cell death, including apoptosis, and suppression of spheroid growth. Comparison of CW and pulsed irradiation modes in PDT with miniSOG showed more pronounced cytotoxic effects of the pulsed mode. Our results suggest that the pulsed irradiation regimen enables enhanced 1O2 production by photosensitizer and stimulates apoptosis. Our results provide more insights into the cellular mechanisms of anti-cancer PDT and open the way to improvement of light irradiation protocols. [Display omitted] •Comparison of CW and pulsed modes of PDT on miniSOG-expressing tumor spheroids was performed.•The pulsed mode resulted in enhanced singlet oxygen production and higher photobleaching rate.•We demonstrated more efficient induction of apoptosis and spheroid growth inhibition under pulsed irradiation.